Endogenous local public good prices in decentralised economies with population mobility and inter-regional transfers - Petchey, Jeffrey; Petchey, J. (School of Economics and Finance, CBS, 2015)
Economic models of regional economies with local public goods, corrective inter-regional transfers and population mobility assume decision-makers are small price takers. We argue this is reasonable for private goods but that local public good prices are in fact endogenous, varying with settlement patterns and hence regional/central policies. Decision-makers should therefore be modelled as having the power to distort policies in order to manipulate public good prices. We show that incentive equivalence in regional economies is sufficient to ensure that known efficiency results, whether the transfer is assigned to regions or the centre, are undisturbed by endogenous local public good prices. However, the corrective inter-regional transfer now includes input price externalities arising from migration which are not accounted for in price taking models. Hence, allowing for endogenous local public good prices extends what we know about the theory of corrective inter-regional transfers.